2014
DOI: 10.1097/jto.0000000000000242
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Tumor, Node, Metastasis Status, and Mutation Rate in Domain of Epidermal Growth Factor Receptor Gene in Serbian Patients with Lung Adenocarcinoma

Abstract: Mutation rate in domain of EGFR gene in investigated lung cancer population is in range with reported data in Caucasian race. Smoking, T descriptor and gender were found to be related to the EGFR status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Indeed, postoperative patients with EGFR mutation show higher efficacy rates to targeted therapy and chemotherapy compared with wild-type patients [21]. Patients harboring EGFR mutation are prone to recurrence in the incision margin [2224], and have a high metastasis rate [25]; however, they still show higher survival after recurrence [2628]. For instance, the 5-year survival rate in patients with EGFR mutation was shown to be higher than that of cases without mutation [21], which may be related to drug sensitivity and comprehensive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, postoperative patients with EGFR mutation show higher efficacy rates to targeted therapy and chemotherapy compared with wild-type patients [21]. Patients harboring EGFR mutation are prone to recurrence in the incision margin [2224], and have a high metastasis rate [25]; however, they still show higher survival after recurrence [2628]. For instance, the 5-year survival rate in patients with EGFR mutation was shown to be higher than that of cases without mutation [21], which may be related to drug sensitivity and comprehensive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the first major study on EGFR mutation status of patients from Serbia, EGFR mutations were detected in 42/360 (11.7%) patients with lung ADC 37 . Contrary to these results, we detected EGFR mutations in a significantly smaller percentage (2/60; 3.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to these results, we detected EGFR mutations in a significantly smaller percentage (2/60; 3.3%). Deletions in exon 19 are most often detected by applying the Cobas® EGFR Mutation Test 35,37 . We did not detect this type of mutation, and the results of our research are most likely the consequence of a smaller number of patients involved in the research, as well as a smaller percentage of EGFR mutated lung ADC.…”
Section: Discussionmentioning
confidence: 99%
“…5 A few retrospective studies with low numbers of patients reported controversial results in African American patients, with mutation rates ranging from 5% to 19% and a significant association with smoking status or sex. [6][7][8][9] With a 36% mutation rate, the results found in our population are much higher than expected in African American populations or white populations of mainland France.…”
Section: Egfr Mutation Ratementioning
confidence: 98%